STUDI SIFAT-SIFAT KIMIA TANAH PADA TANAH TIMBUNAN LAHAN BEKAS PENAMBANGAN BATUBARA - Ernawati, Rika (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Coal mining activities must be followed by reclamation effort. If it was not done, environmental degradation would have occurred such as soil quality changes, not only physically but also chemically. Reclamation conducted by re-vegetation on abandoned mined area (mined out). This research aim is to study chemical soil properties on waste disposal of mined out at PT. Tambang Batubara Bukit Asam (PTBA), South Sumatera. The method of the researches were survey and laboratory analysis. Sampling method use the Purposive Sampling based on age of land. Chemical soil properties were analyzed is Cation Exchange Capacity (CEC), Organic Matter (OM), Base Saturation (BS), available phosphor, nitrogen and available potassium. The result of this research showed that CEC have low to high class (10,98-38,57me/100g) , BS in East of Pit 3 is very high class (97,44-99,80%), whereas West of Pit 3 and North of Pit 1 is very low to low class (8,15-20,16%). OM is very low to low class (0,57-3,45%). Available phosphor is moderate to very high class (20,31-43,67ppm). Nitrogen is very low to low class 0,01-0,12%). Available potassium generally is very high class (66,16-169,12 ppm). Analyze result that prosperity degree based on chemical soil properties namely CEC, BS, OM and phosphor at re-search area have prosperity status is very low to very high.